Creating profitable customers through the magic of data mining. - Ryals, Lynette (Palgrave Macmillan, 2003)
In the early days of relationship marketing, its proponents argued for customer retention on the grounds that this would increase the lifetime value of the customer and, by extension, that this would increase overall corporate profitability. Research, however, has indicated that, for many organisations, a high proportion of customers are unprofitable. This raises a question about the retention proposition. Increasing the retention of unprofitable customers may be damaging, not beneficial, to organisations. This paper discusses some common data analysis techniques used to identify the most and least profitable customers so that marketing managers can develop effective, appropriately targeted customer management strategies.
Keywords: relationship marketing; marketing; customer relations; profitability; data analysis